Ocular morbidity and fuel use: an experience from India. Issue 1 (21st December 2004) - Saha, A; Kulkarni, P K; Shah, A; Patel, M; Saiyed, H N
Abstract : The association of fuel use and ocular morbidity in a village in western India was investigated in a cross sectional prevalence survey involving 469 randomly selected subjects. All subjects were interviewed and underwent medical and ophthalmological examination. Wood use was found to be an important factor in the aetiology of age dependent cataract (OR 2.12, 95% CI 1.03–4.34). When comparing wood only and LPG only users, the odds ratio was 3.47 (95% CI 1.05–11.50). In cases of eye irritation, coal use (OR 2.04, 95% CI 1.13–3.68) and cattle dung use (OR 1.83, 95% CI 1.35–2.47) were shown to be important factors, while male sex posed a lesser risk.